The Role Of Self-Efficacy In The Influence Of Work Ethic And Total Work On Employee Loyalty - Sutianingsih, Sutianingsih; Karina, Salma Rina (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
This study aims to analyze the role of self-efficacy in the influence of work ethic and work totality on employee loyalty at a cosmetic store in Pacitan. There are two variables in this study, namely work ethic (X1) and work totality (X2) as independent variables, intervening variables of self-ability (Z), and work loyalty commitment variables (Y). The population in the study were staff or employees who worked at a cosmetic store. This type of research uses quantitative research by distributing questionnaires. The technique used is the saturated sampling technique. The sample of this study was employees of a cosmetic store in Pacitan totaling 55 respondents. The analysis method uses the path analysis method with the SPSS version 29 application. The results of this study found that self-efficacy, work ethic, work totality, work loyalty have a positive and significant direct effect. There is an indirect and insignificant effect between work totality mediated by self-efficacy on work loyalty.